2018
DOI: 10.1021/acsami.8b17483
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Nanoporous Membranes with Size Selectivity and Charge Rejection from Self-Assembly of Polyelectrolyte “Hairy” Nanoparticles

Abstract: We report the preparation and characterization of charged nanoporous membranes by self-assembly of “hairy” silica nanoparticles (HNPs) functionalized with polyelectrolyte copolymer brushes. We show that HNP membranes possess high water flux, have well-defined pore sizes, and rejection up to 80% of charged species in solution. The properties of these membranes can be tuned by controlling the length and composition of polymer brushes and the electrolyte concentration in solution. We demonstrate that membrane por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
9
2
Order By: Relevance
“…In a previous work, we demonstrated that silica nanoparticles grafted with short polymer brushes can form robust nanoporous membranes via reversible nanoparticle assembly in organic solvents and in water, due to electrostatic and hydrophobic interactions, respectively . We also reported the preparation of charged nanoporous membranes by self-assembly of HNPs functionalized with polyelectrolyte copolymer brushes . We demonstrated that the pore sizes in these membranes undergo changes of up to 40% in response to changes of the ionic strength of the salt solution.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous work, we demonstrated that silica nanoparticles grafted with short polymer brushes can form robust nanoporous membranes via reversible nanoparticle assembly in organic solvents and in water, due to electrostatic and hydrophobic interactions, respectively . We also reported the preparation of charged nanoporous membranes by self-assembly of HNPs functionalized with polyelectrolyte copolymer brushes . We demonstrated that the pore sizes in these membranes undergo changes of up to 40% in response to changes of the ionic strength of the salt solution.…”
Section: Introductionmentioning
confidence: 84%
“…27 We also reported the preparation of charged nanoporous membranes by selfassembly of HNPs functionalized with polyelectrolyte copolymer brushes. 28 We demonstrated that the pore sizes in these membranes undergo changes of up to 40% in response to changes of the ionic strength of the salt solution. We rationalized this behavior by postulating that polymer brushes in the interstitial spaces between HNPs change their conformation similar to polymer brushes grafted inside the nanopores of preformed porous solids.…”
Section: ■ Introductionmentioning
confidence: 86%
“…The transport of ions and molecules in nanochannels and through nanopores has been extensively studied [1][2][3][4][5][6], notably because nanoporous membranes offer attractive features for applications in separation [7][8][9][10][11][12], sensors [13][14][15], catalysis [16,17], or energy storage [17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 163 ] The special 3D nanochannels endowed the separator with a high discharge C‐rate capability (60 mAh g −1 when cathode/anode = 3.5/1.7 mg cm −2 ) compared to common PP/PE/PP separators. Carbon (e.g., mesoporous membranes [ 164,165 ] and porous fibers [ 166,167 ] ) (Figure 7F) and SiO 2 (e.g., self‐assembled nanoparticles [ 168,169 ] ) with 3D nanochannels are common inorganic materials for adjusting ion transport.…”
Section: Nanochannel‐structured Membranesmentioning
confidence: 99%